Modelos de ocupación durante el Paleolítico medio: el nivel K del Abric Romaní (Capellades, Barcelona, España) - Chacón, María Gema; Fernández-laso, María Cristina (Complutum, 2007)
This paper presents the results of the archaeological remains and spatial patterning studies from the Abric Romaní level K. This is the first level of all the stratigraphic sequence where excavation of the whole surface (279 m2) was possible, because there is no disturbance by the ancient excavations (Bartrolí et al. 1995). This interdisciplinary work includes a technological and functional analysis of the lithic industry, a zooarchaeological and taphonomical analysis of faunal assemblages, a spatial patterning and refitting studies of archaeological remains. The main goal is to determine the technical activities realised and their spatial organisation. This kind of study allows us to establish what kind of behaviour and occupation strategies was carried out by the Neanderthals groups. This archaeological level is one example of the spatial structuring degree into the Middle Palaeolithic settlement patterns organisation.
Keywords: Middle Palaeolithic; Abric Romaní; Lithic technology; Faunal assemblage; Spatial patterning; Refittings; Occupation patterns